Hepatoprotective Effect of Vernonia Amygdalina Del. Leaf Ethanol Extract on Male Wistar Rat - Louisa S, Sergia
The liver is the largest internal organ in the body. The liver plays an important role in the metabolism and eliminate endogenous compounds and xenobiotic. Liver is the main organ that are susceptible to drugs induced liver injury. Rifampicin and INH are the first line medication to treat tuberculosis. The long term use of these drugs can cause liver damage. Hepatotoxic effect of those drugs may occur due to the formation of free radicals. Based on literature, Vernonias have antioxidant activity which may scavenge the free radicals and is expected to have hepatoprotective activity. This study was conducted to evaluate the hepatoprotective effect of Vernonia amygdalina ethanolic extracts. Fresh leaves were processed into crude drug then extracted with Soxhlet method in ethanol 96% v/v. The obtained extract was then concentrated and characterized. Hepatoprotective activity were tested on male Wistar rats. Silymarin at a dose of 54 mg / kg bw was used as reference drug. A combination of INH (27 mg/kg ) and rifampicin (54 mg/kg ) were used as an inducer of liver damage and were given orally 1 hour before extract administration. Parameters observed were the activity of the enzyme alanine transferase (ALT), serum albumin level, liver index, as well as hispatological examination. The two doses of the extracts could prevent liver damage, starting on day 14 indicated from ALT level. Based on albumin concentration and ALT activity, the high dose of extract (100 mg/kg) showed more potent as a hepatoprotector compared to low dose (50 mg/kg). Group treated with a high dose showed liver index significant smaller compared to positive control which is indicated a hepatoprotective activity. Through histology examination, liver of rat treated with high dose of extract (100 mg/kg) showed minimal damaged liver’s cells structure which quite similar to normal group. Based on the results, Vernonia amygdalina leaf ethanolic extract that have been corrected from its water content at 46 and 92 mg / kg bw equivalent to dried leaves of african 3.58 and 7.17 grams of the human dose and given consecutively for at least 14 days can prevent liver damage caused by a combination of INH and rifampin.